PENGARUH KOMPENSASI FINANSIAL DAN NON FINANSIAL TERHADAP KOMITMEN KARYAWAN PADA PERUSAHAAN SWASTA DI JAWA TIMUR - Riyadi, Slamet (Program Doktor Ilmu Ekonomi, 2010)
The study empirically of the research to examined the effect of : 1. Financial compensation toward commmitment, 2. Non_financial compensation toward commmitment, and 3. Financial compensation and Non_financial compensation toward commmitment. The Population this research come from 86 employeee’s privat company at East Java Regency, there are from services and trading sector, production sector, and construction sector. The respondent to analysis 71 employees or response rate 83%. The statistical data analysis used here is the Statistical Package for the Social Science (SPSS) Version 15.0. The result indicated that out of the 3 (three) hypotheses proposed, All of them hypotheses can be significantly accepted. 1. The financial compensation was found to have a significant effect on commmitmen at a = 5% and determination coefficient (R2) = 85,6%, 2. Significantly the non financial compensation affected commmitment at a = 5% and determination coefficient (R2) = 94,1%, 3. And the finally the financial compensation and non financial compensation can be significant effect on commmitment at a = 5% and determination coefficient (R2) = 94,1%. Keywords : Financial Compensation, Non_Financial Compensation, and Commmitment